Development of a fully implicit simulator for surfactant-polymer flooding by applying the variable substitution method. (2nd May 2019) - Jia, Zhichun; Li, Daolun; Xue, Zhenggang; Lu, Detang
A perpendicular bisection (PEBI) gridding-based two-phase five-component fully implicit simulator for polymer-surfactant flooding is proposed which utilises the substitution of variable method in the numerical calculation procedure. The substitution of variable method utilises two sets of primary variables based on the phase equilibrium states. When an oil-microemulsion system exists, the primary variables to be solved are the oil phase pressure po and the volume concentrations of oil, polymer, surfactant and salt in the microemulsion, i.e., Com, Cpm, Csm and Cbm . When a single microemulsion is formed, the primary variables are po, Sm, Cpm, Csm and Cbm . A fully implicit iterative scheme is established based on the substitution of variable formulation according to oil phase disappearance or appearance which reduces the number of primary variables. The calculation speed of the new simulator is compared to a conventional fully implicit simulator, which shows that the calculation speed is significantly improved. [Received: January 2, 2017; Accepted: March 22, 2017]